Ovarian response to prostaglandin F2α in lactating dairy cows: A clinical update - Fernando LÓPEZ-GATIUS (The Society for Reproduction and Development, 2021)
Prostaglandin F2α (PGF2α) and its analogs are used to induce luteolysis in estrus synchronization programs to terminate unwanted pregnancies or to promote ovulation in certain cow subpopulations. In the past few decades, the luteolytic dose of PGF2α has remained unchanged. This review explores the clinical implications of increasing the standard dose for these applications in high-producing dairy cows. Ultrasonography may assist in selecting the most appropriate PGF2α dose and improve the results. A reference has been used for PGF2α for promoting ovulation in herds showing poor reproductive performance.